Data interoperability assessment though IFC for BIM in structural design – a five-year gap analysis - Muller, Marina Figueiredo; Garbers, Amanda; Esmanioto, Filipe; Huber, Natan; Loures, Eduardo Rocha; Canciglieri Junior, Osiris (Journal of Civil Engineering and Management, 2017)
In the last years the aec (architecture, engineering and construction) industry has been influenced by the development of building information modelling (bim). With the creation of complex systems, the need for efficient interoperability arises. Based on a study of bim interoperability dimensions and its levels, this research presents an interoperability assessment of bim system in the structural domain, especially considering cast-in-place concrete structures, since they present some special challenges for system interoperability. This assessment was conducted by experiments that imported and exported structural models and structural elements through a non-proprietarz standard for bim models (ifc- industry foundation classes). The experiments were conducted twice, with a five year gap from each other, so the evolution of the interoperability could be assessed as well. The results showed that some special characteristics must be considered in order to achieve efficient interoperability for cast-in-place concrete structures – these structures are monolithic and they have reinforcement steel bars that need detailing. Also, the research showed that in the five-year gap there were evolutions in interoperability, like in object identifiers, which had a considerable improvement. However, some of the major problems remain, such as overlapping of structural parts.